(untitled) (Applied Biological Research, 2023)
Syzigium aromaticum Linn. (clove) essential oil is known for its dental analgesic property, and traditionally used as antiseptic, carminative and as important condiment in foods. Clove essential oil has high medicinal values and its adulteration is done very often with cheap edible oils. The aim of the present study was to characterize the essential oil constituents and determine adulteration in essential oils isolated from the buds of clove. The essential oil composition was determined by GC-MS method and adulteration by ATR-FTIR method. GC-MS analysis of clove essential oil yielded 43 chemical compounds with eugenol (59.16%), β-selinene (9.34%), caryophyllene (7.68%), eugenol acetate (3.35%), and α-humulene (2.16%) as major compounds. The FTIR of isolated clove essential oil showed a characteristic peak at 1514 cm-1, which is missing in market essential oil. The FTIR data of market clove essential oil matches with sesame oil. The clove essential oil was adulterated with sesame oil (0, 5, 10, 20, 30, 40, 50 and 100% v/v), and the FTIR resultant adulterated binary mixtures indicated distinct peaks at 2852.72 and 2924.09 cm-1 (for –C-H sp3 & –C-H sp2 stretching) that is absent in pure essential oil of clove. The present study provides a simple, economic, quick, reliable, and reproducible method for detection of adulteration in clove essential oil. GC-MS analysis further explored the chemical composition of clove essential oil collected from Erbil, Iraq.